Defibrotide in the treatment of hepatic veno-occlusive disease - Fulgenzi A (Dove Medical Press, 2016)
Alessandro Fulgenzi, Maria Elena Ferrero Department of Biomedical Sciences for Health, University of Milan, Milan, Italy Abstract: Hepatic veno-occlusive disease (VOD), also known as sinusoidal obstruction syndrome (SOS), represents the most frequent complication in patients in early phase following hematopoietic stem-cell transplantation (HSCT). In its severe form, VOD/SOS can be associated with multiorgan failure and with a mortality rate >80% by day +100. Defibrotide (DF) (a mixture of 90% single-stranded phosphodiester oligonucleotides and 10% double-stranded phosphodiester oligonucleotides derived from controlled depolarization of porcine intestinal mucosal DNA) has been proposed for the treatment of SOS due to its ability to restore thrombo-fibrinolytic balance and protect endothelial cells. The present review highlights why the mechanisms of action of DF allow its successful use in the prevention and treatment of SOS following HSCT. Keywords: hepatic veno-occlusive disease, hematopoietic stem-cell transplantation, defibrotide